Nepalese Stock Market Volatility During Catastrophic Events (Covid-19) - Dangol, Prashant; Rai, Kristina Chhiling; Sharma, Krish; GC, Alisha; Shrestha, Neha; Khanal, Anuja (New Perspective: Journal of Business and Economics, 2023)
This study investigates the impact of the COVID-19 pandemic on the stock market in Nepal. While prior research has shown the significant impact of catastrophic events on stock market volatility, there is a lack of research specifically examining the Nepalese context. The study aims to explore the effects of the pandemic on stock market performance and volatility, with a focus on the government’s response to the situation. Descriptive statistics, correlation analysis, and hypothesis testing are used to analyze the data and assess stock market volatility, return, and overall performance. The findings suggest that the short-term impact of the COVID-19 outbreak and government policy measures had a significant and adverse effect on stock market volatility, return, and overall performance. This study contributes to the understanding of the Nepalese stock market dynamics during the COVID-19 pandemic and provides insights for investors and policymakers.